Combined toxicity of arsenite and dimethylarsenic acid on the freshwater diatom Nitzschia palea - Ding, Tengda (Ecotoxicology (London, England), 2017)
The toxicity and bioavailability of single arsenic species have been widely investigated, however, the biological effects of mixed arsenic species co-existing in natural waters still remain unknown. The objective of this work was to discern the adverse effects of combined arsenite (As(III)) and dimethylarsenic acid (DMA) on diatom Nitzschia palea. The combined ecotoxicity of As(III) and DMA on N. palea was observed to be time-dependent and showed dose-effect relation. The toxicity of DMA and As(III) mixture was higher than individual DMA or As(III) when the As(III) concentration was in the range of 0.085-0.316 mg L-1. As the As(III) concentration increased from 0.487 to 0.858 mg L-1, the antagonistic effect was found, which could be due to the higher thiols contents in the thiol-containing proteins (e.g., frustulins, silaffins and other glycoproteins). The content of malondialdehyde (MDA) in the treatment of mixed arsenic species was found to be at the same level compared to the As-free control after 72 h of exposure, indicating that the co-toxicity of As(III) and DMA on diatom frustules was not significant. Furthermore, the increase of frustule formation rate in the mixture of EC50 As(III)-EC10 DMA at 72 h exposure time indicated that the damaged diatom cell walls was likely repaired gradually. The results from this study suggested that the effects of co-existed arsenic species were concentration-specific and should be considered in the risk assessment of arsenic and development of water quality criteria for the protection of aquatic ecosystems